Social media usage and its impact on brand equity among SMEs in Malaysia / Syaharizad Abdul Razak, Nor Azrin Md. Latip and Azilahwati Adam - Abdul Razak, Syaharizad; Md. Latip, Nor Azrin; Adam, Azilahwati (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The purpose of this study is to examine the relationship between the factors of usefulness, ease of use, and enjoyment on social media usage and its impact on brand equity of small and medium enterprises (SMEs) in Malaysia. The moderating effect of social media experience was also examined on the relationship between social media usage and brand equity. A research framework was developed based on the Technology Acceptance Model (TAM) and integrated with Customer-Based Brand Equity (CBBE). Data were collected from 212 SMEs in Malaysia using questionnaires. The hypotheses were tested using partial Structural Equation Modelling of Partial Least Squares (PLS-SEM). The findings revealed a significant positive relationship between usefulness, ease of use and enjoyment on social media usage. In addition, the study also found a significant positive relationship between social media usage and brand equity. However, social media experience was found to have no moderating effect on the relationship between social media usage and brand equity. The findings contribute to a better understanding of the determinants of social media usage and its impact on SMEs' brand equity. The findings can encourage and guide SMEs in using social media as a marketing strategy to improve brand equity.